2015
DOI: 10.1530/joe-15-0090
|View full text |Cite
|
Sign up to set email alerts
|

Low glucose-induced ghrelin secretion is mediated by an ATP-sensitive potassium channel

Abstract: Ghrelin is synthesized in X/A-like cells of the gastric mucosa, which plays an important role in the regulation of energy homeostasis. Although ghrelin secretion is known to be induced by neurotransmitters or hormones or by nutrient sensing in the ghrelin-secreting cells themselves, the mechanism of ghrelin secretion is not clearly understood. In the present study, we found that changing the extracellular glucose concentration from elevated (25 mM) to optimal (10 mM) caused an increase in the intracellular Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Oya et al showed that low (1 mM), normoglycemic (5 mM) and high (10 mM) concentrations of d -glucose increased ghrelin secretion compared to 25 mM d -glucose in MGN3-1 cells [38]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oya et al showed that low (1 mM), normoglycemic (5 mM) and high (10 mM) concentrations of d -glucose increased ghrelin secretion compared to 25 mM d -glucose in MGN3-1 cells [38]. …”
Section: Discussionmentioning
confidence: 99%
“…However, inhibitors for SGLT1 and the GLUT family could not confirm an involvement of these proposed glucose-sensors in the effect of d -glucose on octanoyl ghrelin secretion. Previous studies also suggested that ATP-sensitive potassium (K ATP ) channels are involved in the effect of 25 mM d -glucose on ghrelin secretion in MGN3-1 cells [38]. However, tolbutamide (a potassium channel blocker) and diazoxide (a potassium channel activator) neither enhanced nor inhibited 1, 5 or 10 mM glucose-induced ghrelin secretion in primary cultures of gastric mucosal cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…Another metabolic regulatory hormone, ghrelin, is secreted pre-prandially from cells in the gut and is thought to help prepare the body for nutrient uptake (Muller, T. D., et al, 2015). Recently, a ghrelin-expressing cell line was shown to secrete in a manner dependent upon K ATP channels (Oya, et al, 2015). In contrast, using the diazoxide paradigm in primary ghrelin cells, no function was found for K ATP channels in ghrelin secretion (Sakata, et al, 2012).…”
Section: Metabolic Amplification Of Hormone Secretion From Non-β Cellsmentioning
confidence: 99%
“…Dopamine, isoproterenol, oxytocin, muscarine, and prostaglandin (E2) enhance ghrelin secretion, whereas lactate, palmitate, and somatostatin inhibit ghrelin secretion [10,11]. Chemicals, such as cinnamon, and changes in blood glucose levels also regulate ghrelin secretion, suggesting the existence of multiple regulatory mechanisms [12][13][14]. Ghrelin might be associated with gastrointestinal peristalsis, also known as the migrating motor complex, in humans and mice, although no conclusive results have been obtained [15,16].…”
Section: Introductionmentioning
confidence: 99%